The The Food Processing Training Based on Balanced Nutrition Menu for Stunting Children Age 10-15 Years Old : The Food Processing Training Based on Balanced Nutrition Menu - Roziana; Aslis Wirda Hayati; Husnan (STIKes Hang Tuah Pekanbaru, 2021)
Stunting is one of the global nutritional problems, including in Indonesia. This study aims to increase the knowledge and skills of stunting adolescents about processing balanced nutritious food. The activity was carried out face-to-face 5 times. Food supply activities are assessed by means of observation to determine the effectiveness of the counseling provided. Prior to the training, stunting youth knowledge about balanced nutritious food was still low, namely 53% answered questions correctly; Teenagers' knowledge of the basics of food processing based on balanced nutrition is included in the sufficient category, as many as 60% of respondents know about vegetable processing, cooking water, and insight into the food processing profession. After completing the training, adolescents are able to process food based on balanced nutrition, namely providing breakfast, morning snacks, lunch, afternoon snacks, dinner and evening snacks. It is necessary to conduct a campaign about the importance of youth having the skills to organize food.